Chrysopetalids (Phyllodocida: Chrysopetalidae) from the southern Mexican Pacific, including a new species - Cruz-Gómez, Christopher; Bastida-Zavala, J. Rolando (Zootaxa, 2018)
The family Chrysopetalidae has been poorly studied from the Pacific coast of Mexico compared to other families. Specifically from the southern Mexican Pacific, only two species of the family have been recorded in previous studies, Chrysopetalum occidentale and Paleanotus chrysolepis. In this study 311 specimens were revised, and nine species, belonging to six genera were found. Eight of these species are new records from the southern Mexican Pacific coast: Arichlidon watsonae n. sp., Bhawania cf. goodei, Chrysopetalum elegantoides, C. maculata, Hyalopale sp., Paleaequor psamathe, Paleanotus bellis and P. purpurea. A new species is also described, Arichlidon watsonae n. sp., which is characterized by the curved tips blades of the falcigers and their small and ovoid palps. Additionally, the genera Arichlidon and Hyalopale are recorded by first time from the Tropical Eastern Pacific.